Histamine and motivation - Torrealba, Fernando; Riveros, Maria Eugenia; Contreras, Marco; Valdes, Jose Luis (Frontiers in Systems Neuroscience, 2012)
Brain histamine may affect a variety of different behavioral and physiological functions; however, its role in promoting wakefulness has overshadowed its other important functions. Here, we review evidence indicating that brain histamine plays a central role in motivation and emphasize its differential involvement in the appetitive and consummatory phases of motivated behaviors. We discuss the inputs that control histaminergic neurons of the tuberomamillary nucleus (TMN) of the hypothalamus, which determine the distinct role of these neurons in appetitive behavior, sleep/wake cycles, and food anticipatory responses. Moreover, we review evidence supporting the dysfunction of histaminergic neurons and the cortical input of histamine in regulating specific forms of decreased motivation (apathy). In addition, we discuss the relationship between the histamine system and drug addiction in the context of motivation.